Implementing Holistic Mission within The Frame of Religious Moderation - Timotius Sukarna; Ibiang O. Okoi O. Okoi (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2023)
The Indonesian government issued a new concept of the religiosity called religious moderation. Religious conflicts that occur as a result of religious radicalism that arise due to economic, social, and political factors are the reason for the issuance of this discourse. Carrying out the mission holistically is one of the solutions to the problems mentioned above. This article was written with the aim of explaining how to carry out a holistic mission within the framework of religious moderation in Indonesia. Through library studies, this research examines literature related to holistic mission, religious moderation, and related themes. The finding showed that efforts to carry out a holistic mission within the framework of religious moderation in Indonesia can be carried out in a number of ways understanding General Revelation as a media of preaching the Gospel, prioritizing human values, and implementing multicultural education in Christian churches and schools.